Implementasi Manajemen Strategik untuk Meningkatkan Mutu Pendidikan di SMA IT Raudhatul Jannah Cilegon - Faizal Djabidi (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2019)
IT Raudhatul Jannah Cilegon High School seeks to improve quality by implementing Strategy Management through a Process of Analysis, Planning, Implementation and Evaluation where there are problems related to education in schools such as 1) The condition of strategic management in the research area needs to be significantly improved, 2) The Process of Accepting New Students (2) PPDB) not yet based on Academic Information System, 3) Stagnation of Teaching and Learning Activities Processed by Educators 4) Less optimal cooperation between the schools and consumers in this case Higher Education, the Industrial world or companies and local governments so that graduates are not absorbed optimally and efficient. 5) Exploration of Potential Students in the academic and Non-academic fields is not maximal so that the percentage of success has not been achieved by the school. 6) Lack of Realization of School Culture to Create a Religious Environment by Practicing Religion and Life Skills in the Order of School Residents. In this study, the authors used the Qualitative Descriptive method aimed at knowing and understanding the true picture relating to the problems and strategies used by schools in improving the quality of education. The findings in the field that the application of strategic management in schools produce 1) Students excel in Leadership, academic and non-academic achievements both at local and national levels, 2) Educators and Education Personnel qualified according to the competencies set out in Government Policy. 3) External relations and extensive communication in the world of Business and Industry and State and Private Universities. 4) Schools that have religious and theological values, Physiological, Ethical, Aesthetic, Logical and Teleological.